(untitled) ("Conference on Universal Science Research 2023", 2023)
Information protection is an urgent issue of every enterprise today. The damage caused by information security incidents can have a significant impact on the fate of the organization. There are many ways and areas of information security. In this article, we talk about the information security document, which is the main document for ensuring information security in organizations.